Violations Committed by Israel in Armed Conflicts Under International Humanitarian Law - Leatemia, Wilshen (Balobe Law Journal, 2024)
Introductioan: War has various aims and objectives, including under the pretext of self-defense to defend life, family, honor or to defend one's nation, to ideological issues. The wars that occur also often violate international humanitarian law. One of them is between Israel and Hamas.Purposes of the Research: To find out violations of international humanitarian law committed by IsraelMethods of the Research: This research uses an normative juridical research method. Normative Juridical Research is research on Norms, Principles, Rules and Principles based on statutory regulations related to the problem being studied. The approaches used are the statutory approach, the conceptual approach, and case aprroach.Results of the Research: The results of the research show that according to international humanitarian law, violations committed by Israel in armed conflict involve actions that violate the principles of protection of civilians and civilian infrastructure. Humanitarian law, as set out in the Geneva Conventions, prohibits attacks on non-combatants and requires protection of vital facilities such as hospitals and schools, as well as access to humanitarian aid.